O Brother, Where Art Thou? The Effects of Having a Sibling on Geographic Mobility and Labor Market Outcomes - Helmut Rainer; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In most industrialized countries, more people than ever are having to cope with the burden of caring for elderly parents. This paper formulates a model to explain how parental care responsibilities and family structure interact in affecting children?s mobility characteristics. A key insight we obtain is that the mobility of young adults crucially depends on the presence of a sibling. Our explanation is mainly, but not exclusively, based on a sibling power effect. Siblings compete in location and employment decisions so as to direct parental care decisions at later stages towards their preferred outcome. Only children are not exposed to this kind of competition. This causes an equilibrium in which siblings not only exhibit higher mobility than only children, but also have better labor market outcomes. Using data from the German Socio-Economic Panel Study (SOEP) and from the American National Survey of Families and Households (NSFH), we find strong evidence that confirms these patterns. The implications of our results are then discussed in the context of current population trends in Europe and the United States.
Keywords: C13; J14; D19; 330; Geographic Mobility; Intergenerational Relationships; Care of the Elderly; Family Bargaining; Altenhilfe; Arbeitsmobilität; Junge Arbeitskräfte; Familienökonomik; Deutschland; USA